Urochloa ruziziensis desiccation, straw quantity and position on nodulation and production of soybean ‘M-SOY 7908 RR’ - Nepomuceno, M. P. [UNESP]; Silva, B. P. [UNESP]; Giancotti, P. R.F. [UNESP]; Pereira, F. C.M. [UNESP]; Alves, P. L.C.A. [UNESP] (FapUNIFESP (SciELO), 2019)
This study aimed to evaluate the effects of the quantity and soil position of Urochloa ruziziensis straw desiccated with glyphosate for different periods of time on ‘M-SOY 7908 RR’ soybean nodulation, growth and production characteristics. Three experiments were conducted under semi-controlled conditions. In the first, three quantities of U. ruziziensis straw (2.5, 5.0 and 10 ton ha-1) previously desiccated with glyphosate were incorporated into the soil (10 cm deep) or deposited on the soil surface, and in the second experiment, the treatments consisted of three U. ruziziensis desiccation periods, 0, 7 and 12 days before soybean sowing, and one treatment without U. ruziziensis. In the third treatment, desiccation was performed at 0, 5 and 10 days before soybean sowing, and the desiccated plant shoots were removed or left in place before soybean sowing. For each of the experiments, a completely randomized experimental design was adopted, and the masses of the shoot and root dry matter, the degree of nodulation and soybean production were evaluated. The deposition of U. ruziziensis straw on the soil surface promoted the nodulation and growth of ‘M-SOY 7908 RR’ soybean plant shoots, while its incorporation into the soil, even at 2.5 ton ha-1, caused deleterious effects. Desiccation of U. ruziziensis from 0 to 7 days before sowing was also detrimental to the nodulation and growth of M-SOY 7908 RR soybean, reducing its productivity.
Época de dessecação de urochloa ruziziensis, quantidade e posicionamento da palha na nodulação e produtividade da soja ‘M-SOY 7908 RR’
Keywords: Glycine max; Glyphosate; Ground cover; No-till farming